Peningkatan Hasil Belajar Peserta Didik Pada Materi Menyambut Usia Balig Melalui Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation di Kelas IV SD. N. 6 Manggung Jaya - Asdiana A; Dedeh Holipah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Every student has diverse interests and talents. Schools have an obligation to develop the abilities possessed by students. Students' interests and talents will be explored and develops when the school has a management that leads to students, one of which is with the application of a cooperative model of the group investigation type. The innovation of the learning model is a renewal or idea that is expected to have an impact on the learning outcomes themselves. Group investigation is a tool to achieve the set learning objectives. Learning outcomes not as the final destination. along with changes in society and cultural values, as well as changes in The condition and development of students, then the learning style will change. Teachers must understand various models and methods in learning. Through their role, teachers are expected Able to encourage students to always learn in various opportunities through various sources and the media. If the teacher's performance in learning